Evaluación del efecto de la fibra insoluble en el tracto digestivo de cuyes en cebo - Calva Sánchez, Michelle del Rocio (2021)
The guinea pig is a post-gastric fermenting herbivore that, due to its digestive physiology, makes efficient use of fibrous foods. Therefore, the objective this work was to evaluate the effect of different levels of insoluble fiber in the digestive tract of fattening guinea pigs. Two hundred male guinea pigs, with an average weight of 390 ± 96 g, were use. The distribution was randomized with 25 experimental units per treatment. Four isoenergetic and isoproteic diets were formulated (approximately 2700 Kcal/kg of digestible energy and 15 % of crude protein) with levels of 34, 38, 42 and 46 % of neutral detergent fiber (NDF). The variables evaluated were absolute and relative weight of digestive organs, absolute and relative length of small intestine, pH of stomach and cecum. The treatments were compared by applying an analysis of variance, obtaining the following results. Increased of NDF increases the weight of the total digestive tract, being the small intestine and cecum the sections where this effect is observed to a greater extent. Relative weight was higher with the inclusion of 46 % (5.09 % of BW) for the small intestine and 38 % (7.20 % of BW) for the ce- cum. The relative length of the small intestine was higher with the inclusion of 46 % (33.7cm/g BW). The pH of the stomach and cecum did not change, with mean values of 4.1 and 6.6, respectively. The results suggest that the intake of diets with high le- vels of neutral detergent fiber increases the weight and length of the gastrointestinal tract. Key words: absolute weight, insoluble fiber, guinea pig, requirements, relative length.